Biofouling of a unionid mussel by dreissenid mussels in nearshore zones of the Great Lakes. Issue 12 (13th December 2022) - Larson, James H.; Bailey, Sean W.; Evans, Mary Anne
Abstract: In North America, native unionid mussels are imperiled due to factors such as habitat degradation, pollution, and invasive species. One of the most substantial threats is that posed by dreissenid mussels, which are invasive mussels that attach to hard substrates including unionid shells and can restrict movement and feeding of unionids. This dreissenid mussel biofouling of unionids varies spatially in large ecosystems, such as the Great Lakes, with some areas having low enough biofouling to form effective refugia where unionid mussels might persist. Here, we measured biofouling on mussels suspended in cages over the growing season (generally first week in June to last week of August) over 3 years in nearshore areas in Lake Erie (2014–2016), Lake Michigan (Grand Traverse Bay, 2015 and Green Bay, 2016), and Lake Huron (2015). Biofouling varied substantially by years within Lake Erie, with increasingly higher biofouling rates each year. Although dreissenid mussels are present throughout these lakes, we observed very low biofouling in Grand Traverse Bay (Lake Michigan) and Saginaw Bay (Lake Huron), with no dreissenid mussels in 8 of 9 sites across these two bays. Sampling in the rivermouth of the Fox River (Wisconsin) and the Maumee River (Ohio) both showed very high biofouling in areas adjacent to the outlet of these tributaries into Green Bay and Maumee Bay (Lake Erie), respectively. These watersheds are dominated by agriculture, and we would expect high growth of primary producers (i.e., mussel food) and primary consumers (unionids and zebra mussels) in these areas compared to the other sampled bays or the open waters of the Great Lakes. Abstract : Biofouling rates in open water, western Lake Erie sites (LE) were much higher than biofouling rates in open water sites of Saginaw Bay or Grand Traverse Bay. The highest biofouling rates in Maumee Bay (Lake Erie) and Green Bay (Lake Michigan) occurred within 10 km of where the Maumee and Fox Rivers entered these lakes. A moderate positive correlation between biofouling and mussel growth suggests both dreissenid and unionid mussels do better in the same habitats.